The Role Of Financial Capability And Non-Impulsive Behavior In Moderated Mediation Model On The Effect Of Financial Literacy On Financial Well-Being - Tutut Rindiar Gandi; Aula Ahmad Hafidh Saiful Fikri (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This study examines the moderated mediation model to determine the effect between variables partially as well as the role of non-impulsive behavior and financial capability on the effect of financial literacy on financial well-being in the moderated mediation model. This research uses a quantitative approach designed in survey research. The population of this study were students studying higher education in the Special Region of Yogyakarta totaling 129,853 students with the sampling technique using Convenience Sampling. The sample size of this study was 399 students determined by the Slovin formula. The data collection technique used a questionnaire. The instrument validity test is based on Confirmatory Factor Analysis, with the reliability test using Cronbach's Alpha. The data analysis technique uses Conditional Process Analysis with the PROCESS Macro Model 8 syntax developed by Andrew F. Hayes in 2013. The results of this study indicate that: (1) Financial literacy has a positive and significant effect on financial capability; (2) Financial literacy has a positive and significant effect on financial well-being; (3) Financial capability has a positive and significant effect on financial well-being; (4a) Non-impulsive behavior moderates the effect of financial literacy on financial capability; (4b) Non-impulsive behavior moderates the effect of financial literacy on financial well-being; (5) Financial capability mediates the effect of financial literacy on financial well-being.